Peningkatan Pengetahuan tentang Hypnosis di Desa Talang Bukit - Tuhu Perwitasari; Suci Rahmani Nurita; Melda Amalia (3031-8572, 2022)
The nature of a woman is to get pregnant, give birth and breastfeed. Since a woman is born, teenager, pregnant, giving birth, breastfeeding, and menopause, there is always a story behind every process. Pregnancy and childbirth is a dream for all women. There are many stories that accompany every process of pregnancy and childbirth, sometimes there is anxiety and fear in every woman's heart. Sometimes these very apprehensive moments become frightening and even traumatic for some women who are first-time mothers. Lots of expectant mothers become depressed and afraid of not being able to go through it, causing their own trauma. Hypnosis can help mothers to ensure that they feel confident that they are capable of living each stage of life as a woman with the appropriate attachments. Due to the lack of support from family and environment, mothers must always try to create positive conditions for themselves to continue to be oppressed. The method used in this activity is lectures with lieflet media. The result of this activity is to increase mothers' knowledge about hypnosis.